Radiolytic degradation of dodecane substituted with common energetic functional groups. Issue 14 (21st March 2023) - Huestis, Patricia L.; Lease, Nicholas; Freye, Chris E.; Huber, Daniel L.; Brown, Geoffrey W.; McDonald, Daniel L.; Nelson, Tammie; Snyder, Christopher J.; Manner, Virginia W.
Abstract : The relative radiolytic stability of dodecane functionalized with common energetic functional groups was explored with gamma irradiation and probed by various analytical techniques. Abstract : Explosives exist in and are expected to withstand a variety of harsh environments up to and including ionizing radiation, though little is known about the chemical consequences of exposing explosives to an ionizing radiation field. This study focused on the radiation-induced chemical changes to a variety of common energetic functional groups by utilizing a consistent molecular backbone. Dodecane was substituted with azide, nitro, nitrate ester, and nitramine functional groups and γ-irradiated with 60 Co in order to study how the functional group degraded along with what the relative stability to ionizing radiation was. Chemical changes were assessed using a combination of analysis techniques including: nuclear magnetic resonance (NMR) spectroscopy, gas chromatography of both the condensed and gas phases, Raman spectroscopy, and Fourier transform infrared (FTIR) spectroscopy. Results revealed that much of the damage to the molecules was on the energetic functional group and often concentrated on the trigger linkage, also known as the weakest bond in the molecule. The general trend from most to least susceptible to radiolytic damage was found to be D–ONO2 → D–N3 → D–NHNO2 → D–NO2 . These results also appear to be in line with the relative stability of these functional groups to things such as photolysis, thermolysis, and explosive insults.